Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10815-014-0418-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression pattern of glucose metabolism genes correlate with development rate of buffalo oocytes and embryos in vitro under low oxygen condition

Abstract: Purpose This study evaluates the effect of low oxygen conditions (5 Vs 20 %) on buffalo embryo development. Expression patterns of key glucose metabolism genes (HK, PFK, LDH, PDH, G6PDH and Glut1) were assessed in buffalo oocytes and embryos cultured at 5 and 20 % oxygen and correlated with development rate. Methods Maturation rate was observed by determining MII stages by Aceto-orcein method and blastocyst formation was observed at 7 day post insemination (dpi). Expression levels of genes were determined by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
0
13
0
1
Order By: Relevance
“…The results from this study show that, compared to positive and negative controls, 20 μg/mL ginsenoside increased GLUT1 expression. Because high levels of GLUT1 correlate with increased glucose uptake ( Kumar et al, 2015 ), these data indicate that glucose uptake was increased in ginsenoside-treated embryos. Ginsenoside stimulates glucose uptake through two pathways ( Shang et al, 2008 ; Lee et al, 2010b ), including the insulin signaling pathway by promoting the activation of both GLUT1 and GLUT4 ( Shang et al, 2008 ).…”
Section: Discussionmentioning
confidence: 87%
“…The results from this study show that, compared to positive and negative controls, 20 μg/mL ginsenoside increased GLUT1 expression. Because high levels of GLUT1 correlate with increased glucose uptake ( Kumar et al, 2015 ), these data indicate that glucose uptake was increased in ginsenoside-treated embryos. Ginsenoside stimulates glucose uptake through two pathways ( Shang et al, 2008 ; Lee et al, 2010b ), including the insulin signaling pathway by promoting the activation of both GLUT1 and GLUT4 ( Shang et al, 2008 ).…”
Section: Discussionmentioning
confidence: 87%
“…Despite of the existence of evidences showing that the environmental stress created by using a higher oxygen tension during embryo culture may alter the metabolic activity of pre-implantation embryos [ 4 , 41 ], the multivariate statistics we used in our analysis showed that cleavage-stage human embryos grown under both types of oxygen concentration culture conditions left a similar metabolic fingerprint. We failed to observe any change in the net depletion or release of relevant analytes, such as glucose, certain amino acids, fatty acids and glycerophospholipids by human cleavage-stage embryos under either type of culture conditions.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, studies on ETC in oocytes of different species are few [35][36][37] , and the role of NDUFV1, the first complex in ETC that accepts electrons from NADH and is critical for ATP generation, has not been observed in oocytes. In addition, although expression of different LDH isozymes were observed in oocytes and/or CCs of cattle 38 , human 39 , mouse 40 and buffalo 41 , their effects on oocyte maturation had not been carefully analyzed, and particularly, the effects had not been differentiated between DOs and CCs using such a powerful technique as RNAi.…”
Section: Discussionmentioning
confidence: 99%